Hotspots in the grid: Avian sensitivity and vulnerability to collision risk from energy infrastructure interactions in Europe and North Africa. Issue 6 (11th April 2022) - Gauld, Jethro G.; Silva, João P.; Atkinson, Philip W.; Record, Paul; Acácio, Marta; Arkumarev, Volen; Blas, Julio; Bouten, Willem; Burton, Niall; Catry, Inês; Champagnon, Jocelyn; Clewley, Gary D.; et al.
Abstract: Wind turbines and power lines can cause bird mortality due to collision or electrocution. The biodiversity impacts of energy infrastructure (EI) can be minimised through effective landscape‐scale planning and mitigation. The identification of high‐vulnerability areas is urgently needed to assess potential cumulative impacts of EI while supporting the transition to zero carbon energy. We collected GPS location data from 1, 454 birds from 27 species susceptible to collision within Europe and North Africa and identified areas where tracked birds are most at risk of colliding with existing EI. Sensitivity to EI development was estimated for wind turbines and power lines by calculating the proportion of GPS flight locations at heights where birds were at risk of collision and accounting for species' specific susceptibility to collision. We mapped the maximum collision sensitivity value obtained across all species, in each 5 × 5 km grid cell, across Europe and North Africa. Vulnerability to collision was obtained by overlaying the sensitivity surfaces with density of wind turbines and transmission power lines. Results: Exposure to risk varied across the 27 species, with some species flying consistently at heights where they risk collision. For areas with sufficient tracking data within Europe and North Africa, 13.6% of the area was classified as high sensitivity to wind turbines and 9.4% was classified as high sensitivity to transmission power lines. Sensitive areas were concentrated within important migratory corridors and along coastlines. Hotspots of vulnerability to collision with wind turbines and transmission power lines (2018 data) were scattered across the study region with highest concentrations occurring in central Europe, near the strait of Gibraltar and the Bosporus in Turkey. Synthesis and applications . We identify the areas of Europe and North Africa that are most sensitive for the specific populations of birds for which sufficient GPS tracking data at high spatial resolution were available. We also map vulnerability hotspots where mitigation at existing EI should be prioritised to reduce collision risks. As tracking data availability improves our method could be applied to more species and areas to help reduce bird‐EI conflicts. Abstract : We identify the areas of Europe and North Africa that are most sensitive for the specific populations of birds for which sufficient GPS tracking data at high spatial resolution were available. We also map vulnerability hotspots where mitigation at existing EI should be prioritised to reduce collision risks. As tracking data availability improves our method could be applied to more species and areas to help reduce bird‐EI conflicts. Resumo: As turbinas eólicas de geração de energia e as linhas eléctricas podem causar mortalidade de aves devido a electrocução e colisão. Estes efeitos negativos das infrastruturas de energia na biodiversidade podem ser minimizados com a implementação de medidas de planeamento e minimização de impactos. Deste modo, é urgente identificar as áreas de alta risco de colisão e electrocusão para permitir minimizar os impactos negativos das infrastruturas de energia e, simultaneamente, apoiar a transição para uso de energia com baixas emissões carbónicas. Obtiveram‐se localizações de GPS de 1454 aves de 27 espécies susceptíveis a colisão e identificaram‐se as áreas de maior risco de colisão com a infrastrutura de energia para que as aves monitorizadas. A vulnerabilidade das aves às turbinas eólicas e às linhas de transmissão de energia foi determinada tendo em conta a proporção das localizações de GPS obtidas a altitudes que expõem as aves risco de colisão e susceptibilidade a colisões específica de cada espécie. Mapeou‐se a vulnerabilidade máxima de colisã, o para todas as espécies, na Europa e no Norte de África a uma escala de 5 × 5 km. O risco de colisão foi obtido sobrepondo a vulnerabilidade de cada espécie com a densidade de turbinas eólicas e de linhas de transmissão de energia. Resultados: A exposição ao risco de colisão variou para as 27 espécies estudadas. Verificou‐se que a altitude de vôo de algumas espécies colocava‐as em alto risco de colisão. Nas áreas da Europa e do Norte de África com bons dados de seguimentos de aves, identificou‐se que 13.6% têm alta vulnerabilidade a turbinas eólicas e 9.4% têm alta vulnerabilidade a linhas de transmissão de energia. As áreas mais vulneráveis concentram‐se em corredores migratórios importantes e ao longo de áreas costeiras. Os "hotspots" de risco de colisão com turbinas eólicas e linhas de transmissão de energia (dados de 2018) apesar de espalhados por toda a área de estudo têm concentrações elevadas na Europa Central, no estreito de Gibraltar e no Bósforo na Turquia. Síntese e aplicações . Com base em dados de seguimento de aves com tecnologia de GPS identificou‐se as áreas da Europa e do Norte de África em que as populações de aves estão mais vulneráveis a colisões com a infrastrutura eléctrica. Mapearam‐se as áreas com maior risco de colisão com actuais infrastruturas de energia de forma a identificar prioridades para implementação de medidas de mitigação. À medida que aumenta a disponibilidade de dados de seguimento de aves com precisão GPS, será possível identificar e reduzir conflitos com as infrastruturas de energia para mais espécies e em novas áreas.